The mechanism study of quercetin isolated from Zanthoxylum bungeanum maxim. inhibiting ferroptosis and alleviating MAFLD through p38 MAPK/ERK signaling pathway based on lipidomics and transcriptomics - Chen, Yan; Ren, Fajian; Yang, Nannan; Xiang, Qiwen; Gao, Song; Pu, Wei; Yang, Zhou; Liu, Qiuyan; Luo, Shajie; Rao, Chaolong (Frontiers in Pharmacology, 2025)
BackgroundAs a resource with a variety of medicinal and edible values, Zanthoxylum bungeanum Maxim has been found to improve high-fat diet-induced metabolic-associated fatty liver disease (MAFLD).Aim of the studyThe aim of this study was to predict the main active metabolites in Z. bungeanum Maxim. Based on network analysis, and to explore and validate their potential mechanisms of action through lipidomics and transcriptomic techniques.Materials and MethodsMAFLD mouse model and cell model were established to evaluate the effect of active components in Z. bungeanum Maxim. on MAFLD. Serum biochemical indexes, pathological staining observation, lipid group and transcriptome were used to verify the mechanism of action of active components in Z. bungeanum Maxim. on MAFLD.ResultsQuercetin can regulate the liver lipid metabolites of MAFLD mice through the Glycerophospholipid metabolic pathway, thereby improving liver lipid accumulation and liver injury. At the same time, quercetin can also improve MAFLD by reducing oleic acid-induced lipid accumulation in HepG2 cells, and inhibit ferroptosis through the p38 MAPK/ERK signaling pathway, thereby alleviating the progression of MAFLD.ConclusionQuercetin isolated from Z. bungeanum Maxim. has ameliorative effects on MAFLD, probably mainly by affecting lipid metabolic pathways and MAPK signaling pathways.